(Circular) : to the citizens of Burke, Rutherford, Lincoln, Buncombe, and Haywood, (N. Carolina) - Pickens, Israel, 1780-1827 ([Publisher not identified], 1812)
Letter of Israel Pickens to various North Carolina Counties. Pickens discussed the war with Britain, the decision not to have internal taxation and other relevant matters of the time. Also included President Madison's message to the Senate and House regarding the background of the war, and the president's proclamation of war.